Modified basalt fiber early-strength anti-freezing concrete
By using acid etching and nano silica gel liquid modified basalt fibers, and modified natural sand modified by water glass solution, the problems of slow early strength development and poor freezing resistance in low temperature environments are solved, and concrete with high early strength and excellent freezing resistance are achieved, which is suitable for cold areas and winter construction.
Patent Information
- Application Number
- CN202510015396.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional concrete has slow early strength development in low temperature environments and poor freezing resistance, which can easily lead to concrete cracking and degradation of durability.
Basalt fibers that have been etched after acid and then modified with nano silica gel solution are used, and modified natural sand modified with water glass solution is used as fine aggregate. Water glass solution spray is used for maintenance.
It greatly improves the freezing resistance of concrete, makes concrete have high early strength and excellent freezing resistance. It is suitable for cold areas and winter construction, effectively improving the quality and service life of buildings.
Smart Images

Figure CN119797825A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a modified basalt fiber early-strength frost-resistant concrete. Background Art
[0002] As one of the most important building materials, the performance of concrete directly affects the quality and service life of buildings. In cold areas or winter construction, the early strength development and frost resistance of concrete are particularly important.
[0003] Traditional concrete develops its early strength slowly in a low temperature environment and has poor frost resistance, which easily leads to concrete cracking and reduced durability. However, the general method is to use a simple antifreeze agent, which cannot solve the problems of traditional concrete in terms of early strength development and frost resistance. Therefore, the present invention proposes a modified basalt fiber early strength frost-resistant concrete to solve the problems existing in the prior art. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to propose a modified basalt fiber early-strength frost-resistant concrete. The modified basalt fiber early-strength frost-resistant concrete uses basalt fiber modified by nano silica gel after acid etching, and modified natural sand modified by water glass solution as fine aggregate. Water glass solution is used for spraying during maintenance, which greatly improves the frost resistance of the concrete, makes the concrete have high early strength and excellent frost resistance, is suitable for construction in cold areas and in winter, and can effectively improve the quality and service life of buildings.
[0005] To achieve the purpose of the present invention, the present invention is implemented by the following technical scheme: a modified basalt fiber early strength antifreeze concrete, the early strength antifreeze concrete is obtained by concrete slurry through reverse molding and curing, the concrete slurry is prepared by mixing cement, shale ceramsite, modified natural sand, modified basalt fiber, slag mixture, early strength antifreeze agent, water reducer and water in a mass ratio of 15-20:15-20:25-35:8-10:5-8:2-3:3-5:8-10, the modified natural sand is prepared by modifying water glass solution, and the modified basalt fiber is prepared by modifying basalt fiber by nano silica gel solution after acid etching.
[0006] The further improvement lies in that: the water glass solution is prepared by dissolving 5% water glass in water by weight; the nano silica gel liquid is prepared by mixing epoxy resin, nano silica and a cross-linking agent in a mass ratio of 60-65:25-30:5-8, and the cross-linking agent is one of diethylenetriamine, ethylenediamine, triethylenetetramine and methylcycloethylenediamine.
[0007] A further improvement is that: the modified basalt fiber acid etching treatment uses a hydrochloric acid solution with a concentration of 1 mol / L; the basalt fiber has a length of 20 to 30 mm and a diameter of 12 to 14 μm.
[0008] The further improvement lies in that: the slag mixture is prepared by mixing and grinding ore waste slag and ferric nitrate into powder in a mass ratio of 80:20; the water reducer is one of lignin sulfonate water reducer, naphthalene water reducer, melamine water reducer, aminosulfonate water reducer and fatty acid water reducer.
[0009] A method for preparing modified basalt fiber early strength frost-resistant concrete comprises the following steps:
[0010] Step 1: Modification of natural sand: firstly, hydrochloric acid and hydrofluoric acid are made into a mixed acid, then the natural sand is put into the mixed acid for pickling for 40 to 60 seconds, then taken out, rinsed with clean water and dried, then the dried natural sand is immersed in a water glass solution for 1 to 1.5 hours, then taken out and dried, and the modified natural sand is obtained for use;
[0011] Step 2, modification treatment of basalt fiber, first immersing the basalt fiber in a hydrochloric acid solution for 0.5 to 1 hour to obtain acid-etched fiber, then mixing epoxy resin, nano-silica and a cross-linking agent to form a nano-silica silica gel liquid, and finally coating the nano-silica silica gel liquid on the surface of the acid-etched fiber and drying it to obtain modified basalt fiber for standby use;
[0012] Step 3: premixing materials: adding cement, shale ceramsite, modified natural sand, slag mixture, early strength antifreeze agent and water reducing agent into a mixer for premixing to obtain a concrete mixture;
[0013] Step 4: Preparation of concrete slurry: adding water to the mixer in step 3 for mixing and stirring, and finally adding the modified basalt fiber for stirring to fully mix, thereby obtaining concrete slurry;
[0014] Step 5, concrete slurry mold curing, pour the concrete slurry prepared in step 4 into a molding mold for molding treatment, and use water glass solution for spraying and curing after solidification to obtain early strength frost-resistant concrete.
[0015] A further improvement is that the mixed acid in step 1 is prepared by mixing hydrochloric acid with a concentration of 2.9 mol / L and hydrofluoric acid with a concentration of 0.22 mol / L; after rinsing, the mixed acid is treated under ventilation and drying conditions at 80 to 90° C. for 4 to 5 hours.
[0016] Further improvements are: the concentration of the hydrochloric acid solution used in step 2 is 1 mol / L; when coating the nano-dioxide silica gel liquid, the acid-etched fiber is first spread flat on the filter screen, and then the nano-dioxide silica gel liquid is evenly sprayed on the acid-etched fiber to make it evenly wrapped on the surface of the acid-etched fiber, and then it is dried. During drying, the bonded acid-etched fibers need to be twisted apart.
[0017] A further improvement is that the volume concentration of water glass used in step 1 is 5%, and the volume concentration of water glass used for spray curing in step 5 is 3%.
[0018] The beneficial effects of the present invention are as follows: the present invention uses basalt fiber that is acid-etched and then modified by nano-silica gel liquid, and modified natural sand modified by water glass solution as fine aggregate, and uses water glass solution for spraying during maintenance, which greatly improves the frost resistance of concrete, makes the concrete have high early strength and excellent frost resistance, is suitable for construction in cold areas and in winter, and can effectively improve the quality and service life of buildings. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0020] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.
[0021] Example 1
[0022] according to Figure 1 As shown, this embodiment provides a modified basalt fiber early strength antifreeze concrete, which is obtained by concrete slurry through inverted molding and curing. The concrete slurry is made by mixing cement, shale ceramsite, modified natural sand, modified basalt fiber, slag mixture, SBC type early strength antifreeze agent, BASF F10 melamine water reducer and water in a mass ratio of 20:20:35:10:5:3:3:9.
[0023] The modified natural sand is prepared by modifying a water glass solution, wherein the water glass solution is prepared by dissolving 5% water glass by weight in water; the slag mixture is prepared by mixing and grinding ore waste slag and ferric nitrate in a mass ratio of 80:20 into powder.
[0024] The modified basalt fiber is prepared by etching basalt fiber with a length of 20 to 30 mm and a diameter of 12 to 14 μm with a hydrochloric acid solution having a concentration of 1 mol / L and then modifying it with a nano silica gel liquid. The nano silica gel liquid is prepared by mixing epoxy resin, nano silica and diethylenetriamine in a mass ratio of 65:30:5.
[0025] A method for preparing modified basalt fiber early strength frost-resistant concrete comprises the following steps:
[0026] Step 1: First, mix equal volumes of 2.9 mol / L hydrochloric acid and 0.22 mol / L hydrofluoric acid to make a mixed acid. Then, put the natural sand into the mixed acid for pickling for 40 seconds, take it out, rinse it with clean water, and treat it under ventilated drying conditions at 90°C for 4 hours. Then, immerse the dried natural sand in a water glass solution with a volume concentration of 5% for 1 hour, take it out and dry it to obtain the modified natural sand for use.
[0027] Step 2: first immerse the basalt fiber in a hydrochloric acid solution with a concentration of 1 mol / L for 1 hour to obtain an acid-etched fiber, then mix epoxy resin, nano-silica and diethylenetriamine in a mass ratio of 65:30:5 to obtain a nano-silica silica gel liquid, and finally coat the nano-silica silica gel liquid on the surface of the acid-etched fiber and dry it to obtain a modified basalt fiber for use;
[0028] When coating the nano silica gel, first lay the acid-etched fiber flat on the filter screen, then spray the nano silica gel evenly on the acid-etched fiber to make it evenly wrapped on the surface of the acid-etched fiber, and then dry it. When drying, the bonded acid-etched fiber needs to be twisted loose;
[0029] The pore size of the filter screen is larger than the particle size of the nano-silicon dioxide particles.
[0030] Step 3: adding cement, shale ceramsite, modified natural sand, slag mixture, SBC type early strength antifreeze agent and BASF F10 melamine water reducing agent into a mixer for premixing to obtain a concrete mixture;
[0031] Step 4: adding water to the mixer in step 3 for mixing and stirring, and finally adding the modified basalt fiber for stirring to make it fully mixed to obtain concrete slurry;
[0032] Step 5: pour the concrete slurry prepared in step 4 into a molding mold for molding treatment, and after solidification, use a water glass solution with a volume concentration of 3% for spraying and curing to obtain early-strength frost-resistant concrete.
[0033] Example 2
[0034] according to Figure 1As shown, this embodiment provides a modified basalt fiber early strength antifreeze concrete, which is obtained by concrete slurry through inverted molding and curing. The concrete slurry is made by mixing cement, shale ceramsite, modified natural sand, modified basalt fiber, slag mixture, SBC type early strength antifreeze agent, SS-ZF aliphatic water reducer and water in a mass ratio of 18:20:35:8:5:3:3:8.
[0035] The modified natural sand is prepared by modifying a water glass solution, wherein the water glass solution is prepared by dissolving 5% water glass by weight in water; the slag mixture is prepared by mixing and grinding ore waste slag and ferric nitrate in a mass ratio of 80:20 into powder.
[0036] The modified basalt fiber is prepared by etching basalt fiber with a length of 20 to 30 mm and a diameter of 12 to 14 μm with a hydrochloric acid solution having a concentration of 1 mol / L and then modifying it with a nano silica gel liquid. The nano silica gel liquid is prepared by mixing epoxy resin, nano silica and diethylenetriamine in a mass ratio of 64:28:8.
[0037] A method for preparing modified basalt fiber early strength frost-resistant concrete comprises the following steps:
[0038] Step 1: First, mix equal volumes of 2.9 mol / L hydrochloric acid and 0.22 mol / L hydrofluoric acid to make a mixed acid. Then, put the natural sand into the mixed acid for pickling for 40 seconds, take it out, rinse it with clean water, and treat it under ventilated and dry conditions at 90°C for 4 hours. Then, immerse the dried natural sand in a water glass solution with a volume concentration of 5% for 1.5 hours, take it out and dry it to obtain the modified natural sand for use.
[0039] Step 2: first immerse the basalt fiber in a hydrochloric acid solution with a concentration of 1 mol / L for 0.7 h to obtain an acid-etched fiber, then mix epoxy resin, nano-silica and diethylenetriamine in a mass ratio of 64:28:8 to obtain a nano-silica silica gel liquid, and finally coat the nano-silica silica gel liquid on the surface of the acid-etched fiber and dry it to obtain a modified basalt fiber for standby use;
[0040] When coating the nano silica gel, first lay the acid-etched fiber flat on the filter screen, then spray the nano silica gel evenly on the acid-etched fiber to make it evenly wrapped on the surface of the acid-etched fiber, and then dry it. When drying, the bonded acid-etched fiber needs to be twisted loose;
[0041] The pore size of the filter screen is larger than the particle size of the nano-silicon dioxide particles.
[0042] Step 3: adding cement, shale ceramsite, modified natural sand, slag mixture, SBC type early strength antifreeze agent and SS-ZF aliphatic water reducing agent into a mixer for premixing to obtain a concrete mixture;
[0043] Step 4: adding water to the mixer in step 3 for mixing and stirring, and finally adding the modified basalt fiber for stirring to make it fully mixed to obtain concrete slurry;
[0044] Step 5: pour the concrete slurry prepared in step 4 into a molding mold for molding treatment, and after solidification, use a water glass solution with a volume concentration of 3% for spraying and curing to obtain early-strength frost-resistant concrete.
[0045] Example 3
[0046] In this example, the concrete prepared and cured using the traditional antifreeze is tested for performance together with the concrete prepared in Example 1 and Example 2. The raw cement used in the concrete prepared and cured using the traditional antifreeze and the cement used in Example 1 and Example 2 are both cement with a grade of 52.5. The model of the traditional antifreeze used is HW-9 antifreeze. The performance test is shown in Table 1 below.
[0047] Table 1 Concrete performance table
[0048]
[0049] Note: Traditional concrete refers to concrete prepared and cured using the aforementioned 52.5 grade cement, HW-9 antifreeze agent, and sand and gravel aggregate.
[0050] It can be seen from the above table that the concrete prepared in Example 1 and Example 2 is superior to the traditional concrete using only antifreeze in terms of compressive strength in different curing time periods and compressive strength before and after freezing and thawing. This is because the present application uses double-modified basalt fiber as the concrete strength supporting material, firstly acid-etching to increase the specific surface area of basalt fiber, and then using nano-dioxide silica gel to coat the surface of the basalt fiber after acid etching, which greatly increases its surface roughness and improves its adhesion to the matrix; by using water glass solution to modify natural sand and cooperating with subsequent water glass solution spraying and curing, the frost resistance of concrete is greatly improved, and the strength loss of concrete before and after freezing and thawing is reduced.
[0051] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A modified basalt fiber early strength frost-resistant concrete, characterized by: The early-strength antifreeze concrete is obtained by molding and curing concrete slurry through reverse molding. The concrete slurry is prepared by mixing cement, shale ceramsite, modified natural sand, modified basalt fiber, slag mixture, early-strength antifreeze agent, water reducer and water in a mass ratio of 15-20:15-20:25-35:8-10:5-8:2-3:3-5:8-10. The modified natural sand is prepared by modifying water glass solution. The modified basalt fiber is prepared by modifying basalt fiber by nano silica gel solution after acid etching.
2. The modified basalt fiber early strength frost-resistant concrete according to claim 1, characterized in that: The water glass solution is prepared by dissolving 5% water glass in water; the nano silica gel solution is prepared by mixing epoxy resin, nano silica and a cross-linking agent in a mass ratio of 60-65:25-30:5-8, and the cross-linking agent is one of diethylenetriamine, ethylenediamine, triethylenetetramine and methylcycloethylenediamine.
3. The modified basalt fiber early strength antifreeze concrete according to claim 1, characterized in that: The modified basalt fiber acid etching treatment uses a hydrochloric acid solution with a concentration of 1 mol / L; the basalt fiber has a length of 20 to 30 mm and a diameter of 12 to 14 μm.
4. The modified basalt fiber early strength frost-resistant concrete according to claim 1, characterized in that: The slag mixture is prepared by mixing ore waste slag and ferric nitrate in a mass ratio of 80:20 and grinding them into powder; the water reducer is one of a lignin sulfonate water reducer, a naphthalene water reducer, a melamine water reducer, an aminosulfonate water reducer and a fatty acid water reducer.
5. A method for preparing modified basalt fiber early strength frost-resistant concrete, characterized in that The following steps are involved: Step 1: Modification of natural sand: firstly, hydrochloric acid and hydrofluoric acid are made into a mixed acid, then the natural sand is put into the mixed acid for pickling for 40 to 60 seconds, then taken out, rinsed with clean water and dried, then the dried natural sand is immersed in a water glass solution for 1 to 1.5 hours, then taken out and dried, and the modified natural sand is obtained for use; Step 2, modification treatment of basalt fiber, first immersing the basalt fiber in a hydrochloric acid solution for 0.5 to 1 hour to obtain acid-etched fiber, then mixing epoxy resin, nano-silica and a cross-linking agent to form a nano-silica silica gel liquid, and finally coating the nano-silica silica gel liquid on the surface of the acid-etched fiber and drying it to obtain modified basalt fiber for standby use; Step 3: premixing materials: adding cement, shale ceramsite, modified natural sand, slag mixture, early strength antifreeze agent and water reducing agent into a mixer for premixing to obtain a concrete mixture; Step 4: Preparation of concrete slurry: adding water to the mixer in step 3 for mixing and stirring, and finally adding the modified basalt fiber for stirring to fully mix, thereby obtaining concrete slurry; Step 5, concrete slurry mold curing, pour the concrete slurry prepared in step 4 into a molding mold for molding treatment, and use water glass solution for spraying and curing after solidification to obtain early strength frost-resistant concrete.
6. The modified basalt fiber early strength antifreeze concrete according to claim 1, characterized in that: In the step 1, the mixed acid is prepared by mixing hydrochloric acid with a concentration of 2.9 mol / L and hydrofluoric acid with a concentration of 0.22 mol / L; after rinsing, the mixture is treated under ventilation and drying conditions at 80 to 90° C. for 4 to 5 hours.
7. The modified basalt fiber early strength frost resistant concrete according to claim 1, characterized in that: The concentration of the hydrochloric acid solution used in the step 2 is 1 mol / L; when coating the nano-silica silica gel, the acid-etched fiber is first spread flat on the filter screen, and then the nano-silica silica gel is evenly sprayed on the acid-etched fiber to make it evenly wrapped on the surface of the acid-etched fiber, and then dried. During drying, the bonded acid-etched fiber needs to be twisted loose.
8. The modified basalt fiber early strength frost resistant concrete according to claim 1, characterized in that: The volume concentration of water glass used in step 1 is 5%, and the volume concentration of water glass used in spray curing in step 5 is 3%.
Citation Information
Cited By
Water reducer modified basalt fiber reinforced cement concrete and preparation method thereof
CN121850505A